2014
DOI: 10.3389/fendo.2014.00202
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Pig (Sus scrofa) Olfactory Soluble Proteome Reveals O-Linked-N-Acetylglucosaminylation of Secreted Odorant-Binding Proteins

Abstract: The diversity of olfactory binding proteins (OBPs) is a key point to understand their role in molecular olfaction. Since only few different sequences were characterized in each mammalian species, they have been considered as passive carriers of odors and pheromones. We have explored the soluble proteome of pig nasal mucus, taking benefit of the powerful tools of proteomics. Combining two-dimensional electrophoresis, mass spectrometry, and western-blot with specific antibodies, our analyses revealed for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 64 publications
2
62
1
Order By: Relevance
“…We have shown in a previous work (Nagnan-Le Meillour et al, 2014) that around 30 OBP-, VEG-, and SAL-isoforms compose the pig olfactory secretome. Among them, only OBP sensu stricto isoforms were labeled with specific antibodies raised against phosphorylation and O-GlcNAcylation.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…We have shown in a previous work (Nagnan-Le Meillour et al, 2014) that around 30 OBP-, VEG-, and SAL-isoforms compose the pig olfactory secretome. Among them, only OBP sensu stricto isoforms were labeled with specific antibodies raised against phosphorylation and O-GlcNAcylation.…”
Section: Discussionmentioning
confidence: 78%
“…Whether the odorant molecule or the complex OBP/odorant acts as a receptor ligand is still an open question, as none of the two hypotheses have received direct experimental evidence. The recent discovery of OBP isoform diversity in pig (Sus scrofa) nasal mucus (NagnanLe Meillour et al, 2014) favors the hypothesis that OBPs could be more than passive carriers of odorants, being more likely involved in the selection of chemical structures to be presented to a given olfactory receptor. Proteomic analysis of pig nasal mucus revealed that the olfactory secretome (Nagnan-Le Meillour et al, 2014) is mainly composed of around 30 OBP-, VEG-(Von Ebner's Gland protein), and SAL-(Salivary Lipocalin) isoforms, resulting from post-translational modifications (PTMs) of these three gene products and variants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations